Implementation Management of Law No. 33 of 2014 Concerning Halal Product Guarantee in Jambi Province - Nurcahaya, Nurcahaya; Daryanto, Mahbub; Taufiq, M. (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
Management of the implementation of Law No. 33 of 2014 aims to achieve an increase in the making of halal certificates for business people in Jambi province. To find out how the management of the implementation of the law, data collection was carried out with a qualitative approach through interviews, observations, and documentation methods to the Halal Task Force under the Ministry of Religion of Jambi Province. The results of the study found that the management of the implementation of Law No. 33 of 2014 in Jambi Province uses collaborative management. All activities are well planned, and supervision and inspection are carried out by the Halal Product Guarantee Agency (BPJPH), the Halal Examining Agency (LPH), and the Indonesian Ulema Council (MUI) in accordance with the job descriptions listed in the law. The division of tasks is carried out centrally and supervisory authority applies decentrally. Planning, implementation, and supervision involve BPJPH, LPH, MUI, Ministry of Religious Affairs, local government, private sector, and the community. The study recommends that the central and regional governments encourage the acceleration of halal certificates by maximizing socialization in each ministry and providing assistance to micro and small businesses.